Possible mergers and acquisition trends in the financial advisory industry in Singapore and its effects on consumers. - Foo, Chuan Jun. (2008)
This study aims to look at the possible merger and acquisition trends in the financial advisory industry in Singapore and its possible effects on consumers of such services. Our data consists of opinions from prominent figures in the industry.